Analysis of the contributions to the performance of a functional product design using simulation - Reed, Sean; Löfstrand, Magnus; Karlsson, Lennart; Andrews, John (Taylor & Francis, 2016)
Functional products (FP) consist of combined hardware, software and support services that are sold to the customer under performance-based contracts that guarantee a specified level of functional availability. The supplier is responsible for the development, manufacture, support and upgrade of a FP during the contract period. In comparison to a traditional hardware sale only contract, an FP transfers risk from uncertain availability and support costs from the customer to the supplier. This is a major advantage for the customer but means that the supplier must understand and optimise the availability and support costs of a FP design. During product development, simulation can be used to analyse potential FP designs, predict how they will perform and identify possible areas for improvement – providing vital qualitative and quantitative decision support. In this paper, a methodology for analysing a FP design to predict how it will perform and determine the contribution of individual elements of the FP to its overall performance is described. This methodology is then applied to analyse an example of a FP.